The Implications of B-lineage Cells in Kidney Allografts. Issue 10 (October 2020) - Filippone, Edward J.; Farber, John L.
Abstract : The majority of cells comprising the inflammatory infiltrates in kidney allografts undergoing acute and/or chronic rejection are typically T cells and monocyte/macrophages with B cells, plasma cells, and eosinophils accounting for <5%. In a significant minority of biopsies, B lineage cells (B cells and/or plasma cells) may be found more abundantly. Although plasma cell infiltrates tend to be more diffuse, B cells tend to aggregate into nodules that may mature into tertiary lymphoid organs. Given the ability to target B cells with anti-CD20 monoclonal antibodies and plasma cells with proteasome inhibitors and anti-CD38 monoclonal antibodies, it is increasingly important to determine the significance of such infiltrates. Both cell types are potential effectors of rejection, but both also have a tolerizing potential. B cell infiltrates have been associated with steroid resistance and reduced graft survival in some studies but not in others, and their presence should not prompt automatic depletional therapy. Plasma cell–rich infiltrates tend to occur later, may be associated with cell-mediated and/or antibody-mediated rejection, and portend an adverse outcome. Viral infection and malignancy must be ruled out. Randomized controlled trials are needed to determine the appropriateness of specific therapy when B cells and/or plasma cells are found. No strong therapeutic recommendations can be made at this time.